The Role of the Hippo Pathway in Breast Cancer Carcinogenesis, Prognosis, and Treatment: A Systematic Review - Kyriazoglou, Anastasios (Breast Care (Basel), 2021)
BACKGROUND: The Hippo pathway is a developmental pathway recently discovered in Drosophila melanogaster; in mammals it normally controls organ development and wound healing. Hippo signaling is deregulated in breast cancer (BC). MST1/2 and LATS1/2 kinases are the upstream molecular elements of Hippo signaling which phosphorylate and regulate the two effectors of Hippo signaling, YAP1 and TAZ cotranscriptional activators. The two molecular effectors of the Hippo pathway facilitate their activity through TEAD transcription factors. Several molecular pathways with known oncogenic functions cross-talk with the Hippo pathway. METHODS: A systematic review studying the correlation of the Hippo pathway with BC tumorigenesis, prognosis, and treatment was performed. RESULTS: Recent literature highlights the critical role of Hippo signaling in a wide spectrum of biological mechanisms in BC. DISCUSSION: The Hippo pathway has a crucial position in BC molecular biology, cellular behavior, and response to treatment. Targeting the Hippo pathway could potentially improve the prognosis and outcome of BC patients.